Systems Development for Records Archiving and Digital Documents Repository: A Case Study - Gamba, Michael P.; Ocbian, Magdalena M.; Gamba, Maryjean N. (JPAIR Institutional Research, 2014)
The presence of vast communication and information nowadays necessitates the need for a system to readily access and transfer data. The study aimed to develop records archiving and document repository to overcome the barrier of server client method of deploying the documents from one place to another and easier data access to its stakeholders. The Sorsogon State College in the Philippines has four campuses which are located strategically in four municipalities of Sorsogon province. Their distance from each other sometimes causes a problem particularly along communication and real time updates. General User Interface (GUI) of the application has been built on top of all web-enabled computers and even to the mobile devices, so it requires only installed web browsers to render the GUI onto their devices regardless of its platform and specifications. The installation of web-based archiving and repository on its main campus enables satellite campuses to connect to the college private server in a cost-effective manner through virtual private network that connects on top of the Internet service provider. This study overcomes the vulnerability of security by means of allowing user credentials to login at the private server using a 1024 bit Rivest-Shamir-Adleman (RSA) private/public key exchange and 256-bit Advance Encryption System (AES) encryption through its virtual private network. Contents of the uploaded files were being encrypted at 128-bit to prevent intranet users from sneaking the file contents.
Keywords: ICT; document archive; web; GUI; developmental research; Sorsogon City; Philippines